Development and validation of a bioanalytical method using automated solid-phase extraction and LC-UV for the simultaneous determination of lumefantrine and its desbutyl metabolite in plasma. - Lindeg?rdh, N; Annerberg, A; Blessborn, D; Bergqvist, Y; Day, N; White, N (2005)
A bioanalytical method for the determination of lumefantrine (LF) and its metabolite desbutyl-lumefantrine (DLF) in plasma by solid-phase extraction (SPE) and liquid chromatography has been developed. Plasma proteins were precipitated with acetonitrile:acetic acid (99:1, v/v) containing a DLF analogue internal standard before being loaded onto a octylsilica (3 M Empore) SPE column. Two different DLF analogues were evaluated as internal standards. The compounds were analysed by liquid chromatography UV detection on a SB-CN (250 mm x 4.6 mm) column with a mobile phase containing acetonitrile-sodium phosphate buffer pH (2.0; 0.1 M) (55:45, v/v) and sodium perchlorate 0.05 M. Different SPE columns were evaluated during method development to optimise reproducibility and recovery for LF, DLF and the two different DLF analogues. The within-day precisions for LF were 6.6 and 2.1% at 0.042 and 8.02 microg/mL, respectively, and for DLF 4.5 and 1.5% at 0.039 and 0.777 microg/mL, respectively. The between-day precisions for LF were 12.0 and 2.9% at 0.042 and 8.02 microg/mL, respectively, while for DLF 0.7 and 1.2% at 0.039 and 0.777 microg/mL, respectively. The limit of quantification was 0.024 and 0.021 microg/mL for LF and DLF, respectively. Different amounts of lipids in plasma did not affect the absolute recovery of LF or DLF.